Clinical manifestations, laboratory and diagnostic imaging findings of feline upper respiratory and pleural infections - Sim, Juin Jia (2022)
Feline upper respiratory infection and feline pyothorax are common complaints in veterinary practice that can be caused by zoonotic bacteria. The study aimed to characterise clinical features, diagnostic imaging and laboratory findings in cats with upper respiratory tract infection and pyothorax, both retrospectively and prospectively. History, signalment and physical examination information of the cats were obtained. Laboratory findings including haematology, biochemistry, cytology, bacterial identification and diagnostic imaging findings were analysed. Additional virus testings for feline calicivirus, feline herpesvirus, feline coronavirus, feline leukaemia virus and feline immunodeficiency virus were conducted in the prospective study. Results showed that most cats had access to outdoors and were from multi-cat household. In both retrospective studies, common clinical signs such as sneezing, mucoid or mucopurulent nasal discharge and stertorous breathing were predominantly observed in cats with upper respiratory infection; while dyspnoea, harsh or dull lung sound and open mouth breathing were predominantly observed in cats with pyothorax. In the prospective study, nasal discharge, cough and stertor were commonly observed in cats with upper respiratory infection; while abdominal breathing, dehydration and inactivity were observed in cats with pyothorax. Hyperglobulinaemia and hyperproteinaemia were common clinicopathologic abnormalities observed in retrospective cases of feline upper respiratory infection and pyothorax. Additionally, monocytosis and leucocytosis were also common clinicopathologic abnormalities presented in retrospective cases of pyothorax cats. In the prospective study, the majority of the cats with upper respiratory infection or pyothorax had high antibody titres of feline herpesvirus and feline calicivirus, positive for feline coronavirus antibody, negative for feline leukaemia virus antigen and feline immunodeficiency virus. Diagnostic imaging of both retrospective and prospective studies revealed that fluid/soft tissue attenuated turbinates and sinuses were common in cats with upper respiratory infection; while pleural fluid, lung consolidation and obscured cardiac silhouette were common in cats with pyothorax. In retrospective studies, Staphylococcus spp., Pasteurella multocida and Streptococcus spp. were common in cats with upper respiratory infection; whereas, Pasteurella multocida, Streptococcus spp. and Escherichia coli were common in cats with pyothorax. In the prospective study, Pasteurella multocida was the most common bacterium in both upper respiratory infection and pyothorax cases. Beta-lactam group antimicrobials and doxycycline remained suitable choices of antimicrobial treatment in cases of feline upper respiratory infections while amoxicillin–clavulanate showed good antimicrobial susceptibility against aerobic bacteria isolated from the cases in the pyothorax study. The case outcomes of the cats were similar for both diseases. In the retrospective study of cats with feline upper respiratory infection, 15 cats (48.4%) recovered after treatment while 16 cats (51.6%) were dead or euthanised. Whereas, in the retrospective study of pyothorax cats, only 13 cats (46.4%) survived while 15 cats (53.6%) died at the point of re-evaluation. The study contributed to the understanding of feline upper respiratory infection and pyothorax in relation to clinical manifestations and diagnostic imaging features. Moreover, from the bacteria that were isolated, the study highlights the possible risk of zoonotic disease transmission from feline pets to human owners and emphasises the importance of disease prevention.